Acting on information: Performance management for the public sector - Neely, Andrew; Micheli, Pietro; Martinez, Veronica (Cranfield University, 2006)
This briefing examines how public sector organisations can use performance data more effectively to support decision-making and produce improvements in organisational performance. In particular it looks at the challenge of converting performance data into insights and then acting on those insights. Drawing on the academic literature, as well as some notable case studies from the private sector, we have identified five key ‘best practice’ lessons for organisations that want to extract greater insight from their performance data and to ensure that those insights are acted